BUDAYA ORGANISASI PADA DUNIA PENDIDIKAN: SEBUAH TINJUAN LITERATUR REVIEW - Achmad Fadil Firmansyah; Addinnia Dhiya' Ulhaq Nasution; Nurul Fauziyah Rahmawati (Adisam Publisher, 2026)
Organizational culture in educational institutions is a system of values that encompasses norms, beliefs, and customs serving as guidelines for organizational behavior and activities. Organizational culture In modern education, has become a strategic element that influences the performance of educators, the quality of learning, and students’ academic achievement. However, research on this topic remains fragmented and has not yet been comprehensively integrated. This study aims to analyze the concept, determining factors, impacts, and implications of organizational culture through a Systematic Literature Review approach. Data were collected from scientific articles indexed in Google Scholar and Garuda using the keywords “organizational culture,” “educational institutions,” and “education” for the period 2022–2026, with 20 selected articles analyzed systematically. The results indicate that organizational culture is shaped by leadership, ethical values, and organizational communication that continuously internalizes these values. Organizational culture impacts teachers’ performance and motivation, and influences learning quality, academic achievement, and students’ character development. Furthermore, organizational culture serves as a strategy for enhancing the effectiveness and sustainability of educational institutions, influenced by human resource readiness, the organizational environment, and adaptation to technological advancements and social changes. Overall, organizational culture serves as a crucial foundation that requires a holistic, adaptive, and sustainable approach.